Teknologi pengolahan karbol dari limbah cair Serai wangi (cymbopogon nordus) - Ivoni Susanti; Fitria Lestari (Utan Kayu Publishing, 2020)
Serai Wangi is one of the plants that is being developed by the Lubuklinggau City Government and is processed into a variety of products, such as bags, soap, and perfume. Processed products from fragrant Serai Wangi cause environmental byproducts in the form of Serai Wangi liquid waste. This waste if not treated properly will cause problems for the environment, such as unpleasant odors. Therefore, to minimize the emergence of environmental problems, the Serai Wangi waste is processed into carbolic acid which is more beneficial to the community and becomes one of the other sources of income for the people in the district. So, the existence of the Pengabdian Kepada Masyarakat Programme (PKM) that we propose is expected to help the manager of the Serai Wangi and the PKK driving team in the process of making, processing and packaging of Serai Wangi fragrant carbolic waste which has been a problem in the district. In addition, it can overcome pollution and environmental damage and improve the economy of the local district community.